English Education Students’ Perception of the use of Tiktok for Learning Speaking English - Aulfa Reyza Ayuni Prestika (Journal on Education, 2025)
TikTok is one of the popular social media platforms around the world that comes with a variety of interesting features. This study aims to determine students' perceptions of the use of TikTok in learning speaking English. The students are expected to answer 5 questions on the utilization of TikTok as an educational tool in English classes. The result of this research the students concurred that TikTok offers advantages as an excellent educational tool based on the interview findings. TikTok demonstrated its utility as a wonderful additional resource, offering diverse content that enhances comprehension of the subject matter. The pupils believe that the material on this platform enhances comprehension in learning English. Furthermore, TikTok offers supplementary educational resources that are engaging and readily available. There are interactive capabilities in Tiktok application, such duet and stitch video, became significant elements that added an engaging and enjoyable aspect to the learning experience. TikTok markedly enhanced pupils' confidence in English speaking. The students' feedback highlighted that Tiktok served as a transforming environment in which they surmounted early apprehensions regarding fluency. The students articulated that frequent speaking practice enhanced their motivation and confidence in English communication. The analysis revealed a positive association between TikTok usage and enhanced enthusiasm to learn English. The dynamic and interactive characteristics of the TikTok fostered a more stimulating learning environment, prompting students to actively engage with the language. The visual and audiovisual components in TikTok movies enhance the understanding and recall of vocabulary and pronunciation.